Microstructure and transformation related behaviors of a Ni45.3Ti29.7Hf20Cu5 high temperature shape memory alloy - Karaca, H. E.; Acar, E.; Ded, G. S.; Saghaian, S. M.; Basaran, B.; Tobe, H.; Chumlyakov, Yi. (Elsevier Science Sa, 2015)
Effects of heat treatment temperature and time on the microstructure and shape memory behaviors (e.g. transformation temperatures, load-biased shape memory effect, superelasticity, two-way shape memory effect, and related properties) were investigated in a Ni45.3Ti29.7Hf20Cu5 (at%) high temperature polycrystalline shape memory alloy. Heat treatments could be used to control the Us and to a lesser extent recoverable and irrecoverable strains. The Ni45.3Ti29.7Hf20Cu5 alloy was capable of recovering shape memory strains of up to 2% at temperatures above 100 degrees C under high compressive stresses (700 MPa) and up to 0.8% TWSME strain was possible after a non-intense stress-cycling training process. However, due to high Clausius-Clapeyron slopes, large temperature hysteresis, and a strong dependence of transformation stress on temperature, fully recoverable superelastic behavior was not observed because plastic deformation occurred concurrently with the stress-induced martensitic transformation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: NiTiHfCu alloys; Phase transformation; TWSME; Shape memory effect; Shape memory alloys